Improving Students English Competency through The First Rank English Competition - Sulasji, Astri Riance; Herlina, Herlina; S, Sinta (Jurnal Pengabdian Masyarakat Bangsa, 2024)
The Young Generations were the next generations of the nation, which must have a positive impact on the surrounding environment, therefore, English Club Student Organization of Bina Insan University, was holding an English language competition which was beneficial for educational circles in Lubuklinggau, Musirawas and North Musirawas environments. This competition aims to improve students' ability to speak English. Where this competition consists of 4 rounds, namely, true false round, multiple choice rounds, scramble round, and final round. This competition was very well received by students; It can be seen from the number of participants who took part in the competition, which amounted 71 people. This competition runs smoothly and well.